Augmented Reality and Artificial Intelligence for the Assessment and Rehabilitation of Spatial Neglect: A Systematic Review - Li, Shaojun; Chong, Benjamin; Mehri-Kakavand, Ghazal; Shi, Catherine; Taylor, Denise; Fowler, Allan; Billinghurst, Mark; Harvey, Monika; Wang, Alan (SAGE Publications, 2026)
Background and Purpose: Augmented reality (AR) and artificial intelligence (AI) have been applied to the assessment and rehabilitation of post-stroke spatial neglect (SN). This study aims to evaluate the feasibility, effectiveness, degree of personalization, and ecological validity of AR, AI, and hybrid methods for SN assessment and rehabilitation. Methods: PubMed, Scopus, Web of Science, Embase, CINAHL, IEEE Xplore, and the ACM Digital Library were searched up to August 2025. Two reviewers independently screened articles, extracted data, and assessed risk of bias and outcome-level certainty. Results: Of 268 screened studies published between 2000 and 2025, 15 met the inclusion criteria, including 11 assessment studies (8 AI, 1 AR, and 2 hybrid) and 4 AR rehabilitation studies, involving 567 participants. AI assessment methods demonstrated high diagnostic accuracy (area under the curve (AUC) up to 0.95), and 1 AR assessment showed strong diagnostic accuracy (AUC = 0.89). Four AR rehabilitation studies reported acceptable feasibility, with 1 randomized controlled trial (RCT) showing improvements in several neglect outcomes. Ecological validity and personalization were generally very low, and the overall certainty of evidence ranged from low to very low. Conclusion: Current evidence for AR and AI SN assessment and rehabilitation methods remains insufficient to determine their feasibility, effectiveness, ecological validity, and degree of personalization, largely due to small sample sizes, methodological heterogeneity, and the limited number of RCTs. Future research should focus on developing standardized, scalable frameworks that integrate AR with adaptive AI models, and multicenter RCTs are required to confirm clinical efficacy and long-term functional outcomes
Keywords: artificial intelligence; augmented reality; ecological validity; personalized neurorehabilitation; spatial neglect; stroke rehabilitation; 32 Biomedical and Clinical Sciences; 3209 Neurosciences; Clinical Trials and Supportive Activities; Rehabilitation; Networking and Information Technology R&D (NITRD); Clinical Research; Comparative Effectiveness Research; Bioengineering; Machine Learning and Artificial Intelligence; 1103 Clinical Sciences; 1109 Neurosciences; 1702 Cognitive Sciences; Rehabilitation; 3209 Neurosciences